Pengaruh Takaran Arang Sekam Padi dan Bokashi Cair terhadap Pertumbuhan dan Hasil Mentimun (Cucumis sativus L.) - Ignatio Ivanlendi Cunino; Roberto I. C. O. Taolin (Savana Cendana, 2018)
This study aims to determine the effect of rice husk charcoal and liquid bokashi on the growth and yield of cucumber and to know the dosage of rice husk and liquid bokashi appropriate for growth and optimum cucumber yield. The design used in this study was a Factorial Randomized Block Design consisting of two factors with three replications. The first factor is the dosage of rice husk charcoal consisting of three levels ie without rice husk or 0 t / ha, 5 t / ha and 10 t / ha. The second factor is the liquid bokashi dosage consisting of three levels ie without liquid bokashi or 0 ml, 2 ml and 4 ml. The results showed that the interaction effect between rice husk dosage and liquid bokashi occurred only on the ground temperature of 35 days after planting. The dosage of rice husk significantly affected the soil temperature of 14 days after planting, the weight per fruit, the weight of the fruit per plant, the number of fruits per plot, the fresh weight of the stover and the harvest index. The dosage of liquid bokashi has a significant effect on the weight of fruit per plot harvest I and total harvest, the fresh and dry weight of stover. Giving of rice husk 5 tons per hectare gives the best result of 55694 pieces per hectare with weight 16,250 tons. Giving a liquid bokashi of 4 ml per plant yields 53333 pieces per hectare weighing 16,931 tons.